2018
DOI: 10.1002/jmr.2720
|View full text |Cite
|
Sign up to set email alerts
|

Imidazo[1,2‐c]pyrimidin‐5(6H)‐one as a novel core of cyclin‐dependent kinase 2 inhibitors: Synthesis, activity measurement, docking, and quantum mechanical scoring

Abstract: We report on the synthesis, activity testing, docking, and quantum mechanical scoring of novel imidazo[1,2-c]pyrimidin-5(6H)-one scaffold for cyclin-dependent kinase 2 (CDK2) inhibition. A series of 26 compounds substituted with aromatic moieties at position 8 has been tested in in vitro enzyme assays and shown to inhibit CDK2. 2D structure-activity relationships have ascertained that small substituents at position 8 (up to the size of naphtyl or methoxyphenyl) generally lead to single-digit micromolar IC valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…[12,[18][19][20] Many studies on various biomolecular complexes have shown that the use of the SQM methods through each of the methodologies has led to more accurate estimation of complex geometry and binding energy and consequently has increased the docking accuracy. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In this study, a post-docking optimization with the different popular corrected SQM Hamiltonians has been performed for the docking results of a series of human cyclin-dependent kinase 2 (CDK2). The CDK2 is a serine/ threonine-protein kinase that is activated by binding to a regulatory cyclin protein for the cell cycle progression and transcription.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,[18][19][20] Many studies on various biomolecular complexes have shown that the use of the SQM methods through each of the methodologies has led to more accurate estimation of complex geometry and binding energy and consequently has increased the docking accuracy. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In this study, a post-docking optimization with the different popular corrected SQM Hamiltonians has been performed for the docking results of a series of human cyclin-dependent kinase 2 (CDK2). The CDK2 is a serine/ threonine-protein kinase that is activated by binding to a regulatory cyclin protein for the cell cycle progression and transcription.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Furthermore, from the computational point of view, the adequate availability of complex X-ray crystal structures of CDK2 with various ligands (within the ATP binding site) and their affinity data makes CDK2 a very interesting target for docking studies. [17,[20][21][22][23][27][28][29][30] 2 Methods…”
Section: Introductionmentioning
confidence: 99%
“…And B17, B25, and B29 were randomly deprotected to obtain B30−B32. The structures of B1−B32 were further identified by 1 H NMR, 13 C NMR, 19 F NMR, and HRMS. In addition, B7 was dissolved in a mixed solution of ethyl acetate and ethanol, and a single crystal of B7 was obtained by slow crystallization at rt.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…■ ABBREVIATIONS 1 H NMR, 1 H nuclear magnetic resonance; 13 C NMR, 13 C nuclear magnetic resonance; 19 F NMR, 19 F nuclear magnetic resonance; HRMS, high-resolution mass spectrometry; PMMoV, pepper mild mottle virus; CP, coat protein; EC 50 , half-maximal effective concentration; DPI, days post-inoculation; 3D-QSAR, three-dimensional quantitative structure− activity relationship; CoMFA, comparative molecular field analysis; CoMSIA, comparative molecular similarity index analysis; ONC, optimal number of components; SEE, standard error of estimate; Q LOO 2 , cross-validation coefficient; F, Fisher statistic; R 2 , non-cross-validated correlation coefficient; CCC, consistency correlation coefficient; LOO, leave-one-out method; Q 2 , external prediction correlation coefficient; TEM, transmission electron microscopy; MST, microscale thermophoresis; SDS−PAGE, sodium dodecyl sulfate−polyacrylamide gel electrophoresis; K d , dissociation constant; GFP, green fluorescent protein; RT-qPCR, reverse transcription-quantitative polymerase chain reaction…”
Section: Notesmentioning
confidence: 99%
“…The protein structures were prepared using the protein preparation wizard in Maestro with default setting. Grids were generated using Glide, following the default procedure used according to our previous work protocol. ,, The conformational ensembles were docked flexibly using Glide with default setting in both standard precision and extra precision modes. Only poses with low energy conformations and good hydrogen bond geometries were considered.…”
Section: Methodsmentioning
confidence: 99%